Desenvolvimento e aplicação de modelagem eletromagnética em FDTD para estudo da resposta de aterramentos elétricos e linhas de transmissão frente a descargas atmosféricas - Kelvin de Almeida Carvalho (2022)
The finite difference time domain (FDTD) method is widely applied in simulations related to transient analyses involving grounding and transmission lines. The FDTD method can be considered conceptually simple, once its implementation considers the discretization in time and space of the Maxwell curls equations. However, the application of this method presents some challenges, mainly related to long simulation time. In this context, the objective of this work is to apply the FDTD method as the electromagnetic model to study the lightning performance of grounding and transmission lines, considering the representation of soil ionization and the frequency-dependence soil parameters. In order to reduce the simulation time, the application of third order Liao’s and CPML (Convolutional Perfectly Matched Layer) absorbing condition allowed a shorter simulation space and consistent results were obtained for a horizontal grounding electrode buried in a soil with constants parameters. In addition, the application of parallel computation by using the CUDA model applied in a graphic processing unit (GPU) provided an expressive reduction in the simulation time compared with the application of serial computation. Finally, to validate the proposed modeling, extended comparisons were applied based on results generated by the hybrid electromagnetic model (HEM) and reported results of the literature. Consistent results were obtained when the soil ionization was considered, as well as when the effect of the frequency-dependence of soil parameters was assumed. In the latter case, the most significant percentage differences in terms of grounding impulse impedance were 4.67% and 6.35%, respectively, for 1 µs and 4 µs current front-time. In terms of the calculated overvoltages across line insulator strings of 138-kV and 500-kV transmission lines, the differences in comparison to the results provided by the HEM model varied according with the tower-footing grounding resistance and the FDTD technique applied to model the towers.